Comparative Proteomic Analysis Reveals the Ascorbate Peroxidase-Mediated Plant Resistance to Verticillium dahliae in Gossypium barbadense - Lu, Tianxin; Zhu, Liping; Liang, Yuxuan; Wang, Fei; Cao, Aiping; Xie, Shuangquan; Chen, Xifeng; Shen, Haitao; Wang, Beini; Hu, Man; Li, Rong; Jin, Xiang; et al. (Frontiers in Plant Science, 2022)
In previous research on the resistance of cotton to Verticillium wilt (VW), Gossypium hirsutum and G. barbadense were usually used as the susceptible and resistant cotton species, despite their different genetic backgrounds. Herein, we present data independent acquisition (DIA)-based comparative proteomic analysis of two G. barbadense cultivars differing in VW tolerance, susceptible XH7 and resistant XH21. A total of 4,118 proteins were identified, and 885 of them were differentially abundant proteins (DAPs). Eight co-expressed modules were identified through weighted gene co-expression network analysis. GO enrichment analysis of the module that significantly correlated with V. dahliae infection time revealed that oxidoreductase and peroxidase were the most significantly enriched GO terms. The last-step rate-limiting enzyme for ascorbate acid (AsA) biosynthesis was further uncovered in the significantly enriched GO terms of the 184 XH21-specific DAPs. Additionally, the expression of ascorbate peroxidase (APX) members showed quick accumulation after inoculation. Compared to XH7, XH21 contained consistently higher AsA contents and rapidly increased levels of APX expression, suggesting their potential importance for the resistance to V. dahliae. Silencing GbAPX1/12 in both XH7 and XH 21 resulted in a dramatic reduction in VW resistance. Our data indicate that APX-mediated oxidoreductive metabolism is important for VW resistance in cotton.